PEMAHAMAN DAN KESIAPAN UKM DALAM IMPLEMENTASI SAK ETAP : SURVEY PADA UKM DI BEKASI - Cahyati, Ari Dewi; Mulyanti, Kurniawati; Setyawasih, Rianti (JRAK (Jurnal Riset Akuntansi dan Komputerisasi Akuntansi), 2011)
Objective ot this study was to determine whether SMEs in Bekasi has made the financial statement for a basis tax reporting,  basis for decision making in business management, credit application to financial institutions as well as to determine whether SMEs have been aware of any enforcement that ETAP GAAP has become effectively January 1,  2010. The other objective is to determine whether the user  ETAP GAAP in this case SMEs in Bekasi have undertood and prepare for implementation of ETAP GAAP. The research method used is descriptive qualitative. The result show that most of SME in Bekasi has made the financial statements and tax reporting as a basis basis tax reporting,  basis for decision making in business management, credit application to financial institutions (60%).  However most of SMEs (65%) did not know  that ETAP has apply as GAAP effective January 1, 2010. Most of SMEs in Bekasi merely know enough  about the accounting treatment under GAAP ETAP with score 1.8. However, SMEs in Bekasi ready and willing to implelment ETAP GAAP with score 3.